THE EFFECTIVENESS OF HALAL TOURISM PROMOTION IN ENHANCING INDONESIA'S COMPETITIVENESS IN THE GLOBAL MARKET - ari, wisnu ari purwana putra (Berajah Journal, 2024)
Halal tourism has become a significant trend globally, catering to the needs of Muslim travelers who seek destinations that comply with Islamic principles. Indonesia, with its rich cultural heritage and large Muslim population, has immense potential in this sector. This paper examines the effectiveness of Indonesia's promotional strategies in the halal tourism sector and how they contribute to enhancing the country's competitiveness in the global market. Using a mixed-method approach that combines qualitative analysis of promotional materials and quantitative assessment of tourist data, this research highlights the current state of Indonesia's halal tourism initiatives. The findings indicate that while Indonesia has made considerable progress, several challenges hinder its full potential. This paper also suggests targeted strategies for more effective marketing that align with global halal tourism standards, ultimately boosting Indonesia's position as a top halal tourist destination.